Gender-Based Tort: A Case Study of Discrimination Against Women in the Workplace - Irene Puteri Alfani Sofia Sinaga; Adeline Lo; Natasya Edgina Chen; Nicole Baretta; Jerry Shalmont (DiH: Jurnal Ilmu Hukum, 2026)
This study examines gender-based discrimination in Indonesian workplaces, focusing on the unlawful termination of pregnant employees. Despite the existence of comprehensive labour regulations, such as “the Minister of Manpower Regulation No. 3 of 1989, Law No. 13 of 2003, as amended by Law No. 6 of 2023”, and other relevant provisions that guarantee the protection of workers’ rights, discriminatory practices against women continue to occur in various employment sectors. The case study of PT IRNC illustrates how employers unlawfully dismissed pregnant workers on illegitimate grounds, thereby violating their rights and causing both material and moral damages. Using a normative legal approach, this study affirms that such discriminatory actions constitute “a tort under Article 1365” of the Indonesian Civil Code, which holds employers legally accountable to provide compensation and reinstate affected workers. Therefore, gender discrimination in the workplace is not only an employment issue but also a form of tort that requires stricter and more consistent law enforcement. This study emphasizes the importance of increasing legal awareness, compliance, and effective implementation to ensure justice, equality, and the full protection of female workers’ rights within Indonesia’s contemporary labour law framework.